Synthesis, screening and pharmacokinetic evaluation of potential prodrugs of bupropion - Walsh, John (My University, 2014)
In general, prodrugs are developed to circumvent deficiencies associated with the absorption, distribution, metabolism, excretion or toxicological (ADMET) profile associated with the active drug. In our study, we select bupropion, a drug with broad pharmacology incorporating dopaminergic, noradrenergic, nicotinic and cytokine modulation properties, but which is rapidly metabolized in vivo. We exploited its carbonyl and secondary amine functionality to facilitate the synthesis of bioprecursor prodrug forms with the sole objective of identifying analogues with enhanced properties over bupropion. A range of analogues were synthesized, ranging from N-methyl, N-benzyl, oximes, enol acetate and ether forms to examples where both functional groups were utilized to form oxadiazine, oxadiazinone, oxazolone and acetylated derivatives. We then developed an in vitro metabolic screen to simulate the human oral delivery route for these analogues. The selection of media in the screens contained a variety of pH, enzymatic and co-factor systems which mimic metabolic in vivo environments that drugs encounter when delivered orally. By coupling our in vitro screening tool to a selective hyphenated technique such as LC-MS, we were able to quickly select potential prodrugs for further in vitro and in vivo development. From the data generated, the N-alkylated bupropion analogues were shown to have the highest potential to act as bioprecursor prodrugs of bupropion
PUBLISHED
Keywords: Bupropion; Bioprecursor; Prodrug; Microsomes; Plasma; In vitro; Metabolism; Neuroscience